(untitled) (INNOVATIVE ECONOMY, 2021)
Nemish D.V., Humeniuk М.M., Balaniuk I.F., Shelenko D.I. PROSPECTS FOR THE DEVELOPMENT OF SMALL AGRICULTURAL ENTERPRISES OF THE REGION IN THE CONTEXT OF LAND MARKET FORMATION Purpose. The purpose of the article is to reveal the prospects for the development of small agricultural enterprises in view of the transformation processes taking place in the context of land market formation. Methodology of research. Theoretical and methodological basis of the study were legislative and other regulations, scientific works of domestic and foreign scientists on issues related to the functioning of the land market and the development of small enterprises in the agricultural sector. The following general scientific and special methods were used to achieve this goal: abstract and logical method in the formation of theoretical generalizations, assumptions, conclusions; analysis and synthesis in assessing the development of small agricultural entrepreneurship and the functioning of the land market; comparative analysis to compare economic indicators in time and space; graphic method with a visual reflection of the dynamics and structural changes in the distribution of land by ownership. Findings. The research is devoted to a topical issue concerning the prospects for the development of small agricultural enterprises in the context of land market formation. The article pays special attention to aspects of land reform implementation The social and economic preconditions of transformation of the structure of the land fund by forms of ownership are considered. The main restraining factors of agricultural land market development are highlighted. Measures of state support of small agricultural enterprises in the process of land purchase are revealed. The level of efficiency of the land market since its launch is shown. The main positive aspects and problems related to the formation of the land market are presented. The foreign experience of the influence of the land market functioning on the development of small agricultural enterprises is studied. Originality. The substantiation of the dependence of the development of small agrarian entrepreneurship on the level of development of the land market is deepened. Practical value. The implementation of the developed proposals will allow to intensify the development of small agricultural enterprises in the conditions of the land market functioning. It is established that with the support of the state, small agricultural enterprises will receive obvious advantages of development. Key words: small agrarian enterprise, land market, land, land relations, region, land reform.